Perancangan Sistem Informasi Penjualan Online Berbasis Web Di Pixel Computer Prembun - Iswanto, Mukhamad Hasim; saputra, imam wahyu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Pixel Prembun Computer is computer shop that sells laptops, computers and computer spare parts located in the Prembun, Kebumen, Central Java However, in business practice, the store has not used online media in all aspects of the store. Another problem in addition to looking for data on the availability of goods is making reports which is quite slow and time consuming, and what the author highlights the most is low capability of store coverage in attracting consumers which affects to the store profit. Because of the problems above, the author concludes that an online sales information system design is needed. In making this Research Paper, The Author intends to conduct research on online sales information systems at Pixel Computer Prembun, with limitations on the presentation of sales information including product type information with order information facilities, payment confirmations and product checks that author applied with PHP programming language with MySQL database. Based on the results of trials conducted in all the existing menus can run well and the resulting information is effective and accurate. Keywords: Design, Information System, Online Sales, Web